2015
DOI: 10.1177/0192623315598399
|View full text |Cite
|
Sign up to set email alerts
|

Mouse Models of Acute Respiratory Distress Syndrome

Abstract: Acute respiratory distress syndrome (ARDS) is a severe pulmonary reaction requiring hospitalization, which is incited by many causes, including bacterial and viral pneumonia as well as near drowning, aspiration of gastric contents, pancreatitis, intravenous drug use, and abdominal trauma. In humans, ARDS is very well defined by a list of clinical parameters. However, until recently no consensus was available regarding the criteria of ARDS that should be evident in an experimental animal model. This lack was re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
60
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(65 citation statements)
references
References 147 publications
4
60
0
1
Order By: Relevance
“…pneumonia, inhalation injury, aspiration of gastric contents, pulmonary contusion, or reperfusion pulmonary edema) or indirect (e.g. sepsis, burn, major trauma with shock, multiple blood transfusions, or acute pancreatitis) [1, 2, 4]. ARDS in humans is defined by a list of clinical parameters including diffuse alveolar damage and reduced pulmonary oxygenation [1, 2, 5, 6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…pneumonia, inhalation injury, aspiration of gastric contents, pulmonary contusion, or reperfusion pulmonary edema) or indirect (e.g. sepsis, burn, major trauma with shock, multiple blood transfusions, or acute pancreatitis) [1, 2, 4]. ARDS in humans is defined by a list of clinical parameters including diffuse alveolar damage and reduced pulmonary oxygenation [1, 2, 5, 6].…”
Section: Introductionmentioning
confidence: 99%
“…Mouse models of sepsis-induced inflammatory lung injury can be used to improve understanding of the mechanisms that control sepsis-induced lung injury and subsequent repair [4, 11]. It is therefore desirable for such mouse models to recapitulate the pathogenesis of human ARDS as closely as possible.…”
Section: Introductionmentioning
confidence: 99%
“…Preparation of quality lung tissue samples is important for histopathologic examination to optimize preservation of fine pulmonary architecture and, in the case of immunostaining, antigenicity of target epitopes [11][12][13]. A study by Engel and Moore identified more than 60 variables in this time frame, beginning with proper sample collection and handling and including multiple aspects of tissue collection, fixation, processing, embedding, slide drying, and storage [14].…”
Section: Factors That Influence Evaluationmentioning
confidence: 99%
“…To collect lungs for histology, samples should be harvested as soon as possible following death to minimize autolysis [11]. Autolysis ("self-digestion") is a postmortem change characterized by degradation of cellular constituents (DNA, RNA, protein) and dissolution of the tissue [15].…”
Section: Factors That Influence Evaluationmentioning
confidence: 99%
“…However, barrier disruption differs with injury type. Pulmonary edema causes pulmonary interstitium thickening and alters the gas exchange process by increasing the distance for gas exchange to occur (43), whereas lipopolysaccharide-induced acute lung injury predominantly damages pulmonary microvascular endothelial cells and destroys their barrier function, thereby causing inflammatory cell aggregation, adhesion, exudation and secretion of various inflammatory cytokines and chemokines (44). As a result, the blood barrier is further damaged.…”
Section: Perturbing Effects Of Seawatermentioning
confidence: 99%